Fast parallel lexical analysis on multi-core machines. (2016) - Barve, Amit; Joshi, Brijendra Kumar
Lexical analysis begins the process of compilation of any source program. Various attempts have been made to improve the lexical analysis phase by exploiting the inherent parallel processing capability of multi-core machines. In this paper we present a fast lexical analysis algorithm that performs better than our previous algorithm which uses round robin approach for scheduling jobs to processors. We demonstrate the improvement in lexical analysis phase by automatically generating C programs having up to 300 potentially parallel constructs like if..else, for, while loops, switch..case, etc. The maximum speedup achieved for seven CPUs is 4.14.